Nutritional and biological value of canned pate from japanese sardine Sardinops melanostictus - L. V. Shulgina; K. G. Pavel; E. A. Solodova; E. V. Yakush (Известия ТИНРО)
Nutritional and biological value and the dietary lipid indices are determined for 2 recipes of pate canned food from japanese sardine Sardinops melanostictus (sardine-iwashi). The first recipe uses the fish and vegetable raw materials, but the second one includes additionally vegetable oil used for sautéing of the vegetables. The content of proteins in both products was 13.7–15.5 %, fat content — 14.3–17.4 %, carbohydrates — 4.6–4.8 %. The proteins were completed and balanced in terms of amino acid composition. The lipids were represented mainly by triacylglycerides, the portion of phospholipids was 6.0–6.4 %. Among fatty acids of the lipids, the most numerous group was PUFAs (38.8 % of the total amount of fatty acids for the 1st recipe, 41.3 % — for the 2nd recipe). The PUFAs amount in 100 g of canned food was 5.86 and 7.05 g, respectively. The content of omega-3 and omega-6 PUFA was 25.2 % and 9.9 % of the total number of fatty acids for the 1st recipe and 18.6 % and 20.5 % for the 2nd recipe. Among PUFAs, eicosapentaenoic acid (20:5 n-3) dominated in the pate of the 1st recipe (14.2 %) but linoleic acid (18:2 n-6) dominated for the 2nd one (19.6 %). The sum of eicosapentaenoic and docosahexaenoic acids was 19.0 % of total fatty acids or 3.14 g/100 g of the pate for the 1st recipe but 14.1 % or 2.40 g/100 g for the 2nd recipe. The dietary indices (or health lipid indices) were determined as the ratio of certain saturated and unsaturated fatty acids in the product. The indices of atherogenic- ity and thrombogenicity were 0.59 and 0.24 for the 1st recipe and 0.41 and 0.24 for the 2nd recipe, respectively. The hypocholesterolemic index was evaluated as 2.26 and 3.49 for the 1st and 2nd recipes, respectively. Low values of atherogenicity and thrombogenicity and high value of hypocholesterolemic index provide positive effect of the lipid profile on cholesterol metabolism and rate of thrombosis in the human blood vessels.